Multiple tuned liquid column dampers for torsional vibration control of structures theoretical investigation. - Xu, Y.L (Earthquake engineering & structural dynamics.)
This paper presents a theoretical investigation on the performance of multiple tuned liquid column dampers (MTLCD) for reducing torsional vibration of structures in comparison with single tuned liquid column dampers (STLCD). The analytical model is first developed for torsional vibration of a structure with an MTLCD under either harmonic excitation or white noise excitation. The experimental results are then used to verify the analytical model for coupled MTLCD-structure systems under harmonic excitation. The performance of an MTLCD and its beneficial parameters for achieving the maximum torsional response reduction to white noise excitation are finally investigated through an extensive parametric study in terms of the distance from the centre line of the MTLCD to the rotational axis of the structure, the ratio of the horizontal length to the total length of liquid column, frequency bandwidth, head loss coefficient, the number of TLCD units in an MTLCD, frequency turning ratio and the spectral level of excitation moment. The results show that there is an optimal head loss coefficient and an optimal frequency bandwidth for an MTLCD to achieve the maximum torsional response reduction. It is also demonstrate that the sensitivity of an optimized MTLCD to the frequency tuning ratio is less than that of an optimized STLCD, and it can be further improved by increasing the bandwidth but at the cost of less torsional vibration reduction.